Engaging Multimedia into Speaking Class Practices: Toward students’ Achievement and Motivation - Ratnawati Ratnawati; Didih Faridah (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2017)
The present study reports several impacts of implementing multimedia toward teaching and learning process in speaking class at second grade students of Galuh University, Ciamis. Further, the study came from insights on students’ boredom during speaking class which affected their achievement and motivation. Mixed method research design (Creswell, 2013) then employed to answer several proposed hypotheses. For proving the result of its application, observation, questionnaire, pre and post-test were administered to collect the data while both quantitative and qualitative approaches were applied to analyze the collected data from classroom practices. The research findings indicates that multimedia in speaking class got positive responds from students in term of motivation and accomplishment. The great look portrayed from the class that students were enthusiastic, got involved and interested in multimedia provided by teacher during learning process. Moreover, pre and post-tests that are performace-based tests were greatly used to test the effectiveness of multimedia effects during the class. In this side, the researcher employed experiment of two equivalent groups: control and experimental group. It then reported that t-test related is 2.04 out of 1.70 for t- distribution which points out that there is significant difference between the results of both tests. It means that the result of this research agreed that multimedia has good effects for teaching speaking in the scope of students’ interests, feedback and their cognitive aspects. In line with above statements, the further studies is also necessary dealing with other multimedia for obtaining more positive effects toward learning process and those result enables to increase quality of education.